Prevalence of Musculoskeletal Disorders and Ergonomic Risk Factors among Firefighters - Hamza Farooq, Montakarn Chaikumarn, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Injury to the musculoskeletal system or the human body's ability to move is known as a musculoskeletal disorder (i.e. muscles, tendons, ligaments, nerves, discs, blood vessels, etc.). Firefighting is a physically hard and dangerous job. Firefighters carry out emergencies and prevent fire and respond to disaster. Workers who deal with fireworks often have musculoskeletal disorders. Aim: To investigated the prevalence of musculoskeletal disorders and ergonomic risk factors among firefighters. Methodology: Nordic musculoskeletal questionnaire was used to report musculoskeletal disorders in 106 firefighters and quick exposure check (QEC) questionnaire was used in 20 firefighters for 3 different tasks to evaluate the ergonomic risk factors. Results: Firefighters experienced low back pain as major pain in last 12 months followed by shoulder and neck pain. Low back pain along with knee pain caused trouble in working in last 12 months. While pain in last 7 days were low back pain followed by knee and upper back pain. Task of lifting ladders on shoulder was the major ergonomic risk factor for developing musculoskeletal disorders as compared to holding up hose and folding the hose task. Conclusion: High prevalence was shown in low back, knees, neck and shoulder. Lifting up ladders on shoulder task leads to ergonomic risk for development of musculoskeletal disorders. Keywords: Firefighters, musculoskeletal disorders, ergonomic risk factors, QEC (quick exposure check), Nordic musculoskeletal questionnaire.